Roles of carbon nanotubes in novel energy storage devices - Sun, Leimeng (2018)
Carbon nanotubes (CNTs), a typical one-dimensional carbon material, have been extensively studied for electrical and electronic applications for more than two decades. Owing to their unique morphology and outstanding electrochemical characteristics, CNTs are of promising potentials in energy storage applications. CNTs have been incorporated into the electrodes of batteries and supercapacitors as an active material and supporter. In recent years, the functions of CNTs in these energy storage devices have undergone a dramatic change. In this review, we summarize the roles of CNTs in novel energy storage devices, especially in Lithium-ion batteries and electrochemical supercapacitors. The new functions of CNTs in binder-free electrodes, micro-scaled current collectors and flexible and stretchable energy storage devices are also discussed.